2022
DOI: 10.1097/gme.0000000000001928
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian insufficiency and secondary amenorrhea in a patient with a novel variant within GDF9 gene

Abstract: Objective: Premature ovarian insufficiency is a heterogeneous condition that can be caused by several factors, such as genetic, environmental, etc. and represents one of the main causes of female infertility. One of the genes implicated is GDF9, which encodes a member of the transforming growth factor-beta superfamily that participates in the coordination of somatic cell activity, female fertility, including folliculogenesis, and oocyte maturation.Damaging variants in GDF9-encoded growth factors can cause the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Among TGFβ superfamily members, oocyte-derived growth differentiation factor 9 (Gdf9) and Bmp15 are essential for folliculogenesis in mice [ 73 ]. In human genetic studies, GDF9 and BMP15 variants are found in women with premature ovarian failure and amenorrhea [ 74 , 75 , 76 ], suggesting that GDF9 and BMP15 could be potential PCSK6 substrates in the ovary.…”
Section: Findings From Pcsk6 Knockout (Ko) Micementioning
confidence: 99%
“…Among TGFβ superfamily members, oocyte-derived growth differentiation factor 9 (Gdf9) and Bmp15 are essential for folliculogenesis in mice [ 73 ]. In human genetic studies, GDF9 and BMP15 variants are found in women with premature ovarian failure and amenorrhea [ 74 , 75 , 76 ], suggesting that GDF9 and BMP15 could be potential PCSK6 substrates in the ovary.…”
Section: Findings From Pcsk6 Knockout (Ko) Micementioning
confidence: 99%